Validity of Endoscopic Submucosal Dissection for Gastric Cancer Diagnosed as Differentiated Adenocarcinoma Before Treatment Regardless of Lesion Size - Nomura, Kosuke; Hoteya, Shu; Ochiai, Yorinari; Okamura, Takayuki; Suzuki, Yugo; Hayasaka, Junnosuke; Mitsunaga, Yutaka; Tanaka, Masami; Fuchinoue, Kazuhiro; Odagiri, Hiroyuki; Yamashita, Satoshi; Matsui, Akira; et al. (Turkish Journal of Gastroenterology, 2023)
Background/Aims: We investigated the validity and safety of endoscopic submucosal dissection for gastric tumors by examining shortand long-term outcomes by tumor diameter. Materials and Methods: Endoscopic submucosal dissection for gastric tumor was performed on 4259 lesions at our hospital between January 2005 and June 2021. [Study 1] Patients were divided into 5 tumor diameter groups: 3751 lesions, ≤30 mm; 366 lesions, 31-50 mm; 106 lesions, 51-75 mm; 24 lesions, 76-100 mm; and 12 lesions, ≥101 mm. Short-term gastric endoscopic submucosal dissection outcomes were investigated. [Study 2] Long-term outcomes (delayed gastric emptying and prognosis) were investigated in 508 cases with tumor diameter ≥31 mm. Results: [Study 1] Perforation rate (%) was 1.2, 3.6, 3.8, 12.5, and 25.0 for lesions with tumor diameter ≤30 mm, in the range 31-50 mm, 51-75 mm, and 76-100 mm, and ≥101 mm, respectively. Postoperative bleeding rate (%) was 4.8, 9.0, 6.6, 20.8, and 33.3, respectively, R0 resection rate (%) was 96.8, 90.2, 89.6, 70.8, and 66.6, respectively, and curative resection rate (%) was 92.0, 61.2, 63.2, 45.8, and 8.3, respectively. [Study 2] There were 7 cases of delayed gastric emptying after wide resection, with 3 patients requiring balloon dilatation, 1 of whom subsequently underwent distal gastrectomy. Among 205 cases of noncurative resection, 110 underwent additional surgery, residual cancer was present in 11 cases, and lymph node metastasis was observed in 7 cases (1 patient died of disease). To date, 1 of the 95 patients being followed up has died of disease (mean follow-up: 2042 days). Conclusion: Even with a tumor diameter ≥31 mm, curative resection was achieved in about 60% of cases in which intramucosal lesions were considered possible preoperatively, but the rate was low at 8.3% for tumor diameter ≥101 mm. Long-term outcomes appear favorable, with only 0.4% of the patients dying of disease but delayed gastric emptying observed in 1.7% of cases. Cite this article as: Nomura K, Hoteya S, Ochiai Y, et al. Validity of endoscopic submucosal dissection for gastric cancer diagnosed as differentiated adenocarcinoma before treatment regardless of lesion size. Turk J Gastroenterol. 2023;34(11):1143-1149.